Understanding Of Children’s Privacy Rights Protection In Sharenting Practice On Social Media - Purnamasari, Rika; Dulnasir (MultiTech Publisher, 2023)
Sharenting is a new phenomenon resulting from the increased activity of social media users. Sharenting is an activity to share children’s activities and lives uploaded on social media. Sharenting activities negatively impact children because all types of activities uploaded on social media are not with the children’s approval. The research objective is to examine parents’ understanding of violations and protection of children’s privacy in sharenting practices on social media and to investigate violations committed by parents in sharenting activities. This research employed a descriptive qualitative method with parent respondents who actively used Instagram social media and worked as local Purwakarta celebgrams. Data collection used observation and interviews and was analyzed by data reduction, presentation, and verification. The research results revealed that sharenting activities were often carried out by parents and were published on the Instagram social media platform for various reasons and motives. The sharenting practice was sharing videos and photos of daily life and the growth and development of children periodically. Sharenting activities were also carried out because parents did not understand the negative impact on children’s privacy and lacked insight into government regulations on children’s privacy rights violations.